Research on Computer Network Security in Cloud Computing Environment - Qi, Gang (Journal of Theory and Practice of Management Science, 2025)
With the rapid development of China's social economy and the continuous improvement of the level of science and technology, information technology and big data technology are also developing rapidly. Cloud computing has been widely used in various fields of people's daily life and work and occupies a very important position in social production and life. Based on this, combined with the development and application background of cloud computing, this paper discusses the main problems faced by computer network security and tries to put forward corresponding security prevention technology to promote the construction of a high-quality environment under the cloud computing environment and ensure the security of information and data applications.